Constraints, Normative Ideal, and Actions to Foster Change in the Practice of Nursing: A Qualitative Study. (October 2020) - Martin, Patrick; Bouchard, Louise
Abstract : The purpose of this study was to explore the lived experiences of politically engaged hospital staff nurses, the way in which they would like to practice, as well as the ideas and actions they have undertaken to foster change in their nursing practice. A qualitative design was used to collect data from a purposive sample of 39 nurses. Results indicate a deprofessionalization of nursing and a drift toward authoritarianism. There are, nonetheless, nurses who employ acts of resistance with the aim of establishing new power relations. It appears that those actions must focus on the radical renewal of democracy in hospitals.